1993
DOI: 10.1182/blood.v82.11.3265.bloodjournal82113265
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant granulocyte colony-stimulating factor administration to healthy volunteers: induction of immunophenotypically and functionally altered neutrophils via an effect on myeloid progenitor cells

Abstract: We performed a detailed kinetic study on the in vivo effect of a single subcutaneous dose of granulocyte colony-stimulating factor (G-CSF; 300 micrograms) in four healthy individuals on the expression and function of neutrophil Fc gamma receptors (Fc gamma R). G-CSF did not induce Fc gamma RI (CD64) on circulating neutrophils. However, neutrophils newly formed in response to G-CSF were Fc gamma RI positive and were able to perform antibody-dependent cellular cytotoxicity in an Fc gamma RI- dependent way. Fc ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 0 publications
6
41
0
Order By: Relevance
“…β2‐Integrins, like the CD11b/CD18 complex, do not seem to be required for polymorphonuclear leukocyte (PMN) adherence and are more relevant for chemotaxis. Yet some authors observed that increased expression of these integrins may increase PMN adherence 20,21 , 37 . After priming with G‐CSF, other groups did not find any changes in CD11b expression 11,23 , 38 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…β2‐Integrins, like the CD11b/CD18 complex, do not seem to be required for polymorphonuclear leukocyte (PMN) adherence and are more relevant for chemotaxis. Yet some authors observed that increased expression of these integrins may increase PMN adherence 20,21 , 37 . After priming with G‐CSF, other groups did not find any changes in CD11b expression 11,23 , 38 .…”
Section: Discussionmentioning
confidence: 95%
“…CD11b/CD18 plays an important role in neutrophil functional properties such as migration. Although some authors describe increased expression of CD11b/CD18 after G‐CSF treatment 20,21 others report no significant changes 11,22 . Associated functions such as phagocytosis 4,9 , 23 and reactive oxygen species (ROS) production 4,22‐24 were found to be enhanced after administration of filgrastim or lenograstim.…”
mentioning
confidence: 99%
“…Such a delayed decrease in WBC and PMN levels has also been demonstrated by another research group 16 . The reason for this is unclear but may be due to some immunophenotypical or functional changes in mature neutrophils and their precursor cells 20‐25 . Neutrophils produced in vivo in response to G‐CSF demonstrated an enhanced adherence capacity and increased migration across the vascular endothelium 21,23 .…”
Section: Discussionmentioning
confidence: 70%
“…Neutrophils produced in vivo in response to G‐CSF demonstrated an enhanced adherence capacity and increased migration across the vascular endothelium 21,23 . These effects were detectable after administration of a single standard dose (300 µg) of G‐CSF, 22 and they persisted much longer than the increased neutrophil counts 20,22 , 25 . Thus, the slight drop in peripheral blood WBC and PMN counts might not be due to storage depletion or impaired marrow function, but to altered distribution of these cells in the donor.…”
Section: Discussionmentioning
confidence: 99%
“…G–CSF begins to increase the donor's WBC count within 4 hours after the first dose is given, 31 but the increase in blood HPCs is delayed. The concentration of CD34+ cells in the blood begins to increase after 3 days of G–CSF and reaches a peak after 5 or 6 days.…”
Section: Donation Of Pbpc Concentratesmentioning
confidence: 99%